Analisis Peran Influencer Marketing dalam Membangun Brand Awareness dan Kepercayaan Konsumen pada Generasi Z - Iwan Iwan; Purwatiningsih Purwatiningsih; Sopyan Sopyan (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study aims to examine the influence of influencer marketing in increasing brand awareness and consumer trust among generation Z with a case study of Scarlett Whitening. Using quantitative methods, this study tests the hypothesis through path analysis. The results show that influencer marketing has a significant influence on brand awareness and consumer trust. Influencer credibility, authenticity, and engagement are the main factors in forming positive perceptions of the brand. Scarlett Whitening utilizes this marketing strategy through collaboration with macro and micro influencers, interactive content presentation, and consistency in brand communication. These findings confirm that influencer marketing is an effective promotional strategy in increasing brand awareness and building trust, especially among generation Z who are more active in digital media. Further research is recommended to explore other factors that can influence consumer behavior in the digital era.